2020
DOI: 10.1111/ppl.13185
|View full text |Cite
|
Sign up to set email alerts
|

Ion homeostasis for salinity tolerance in plants: a molecular approach

Abstract: Soil salinity is one of the major environmental stresses faced by the plants. Sodium chloride is the most important salt responsible for inducing salt stress by disrupting the osmotic potential. Due to various innate mechanisms, plants adapt to the sodic niche around them. Genes and transcription factors regulating ion transport and exclusion such as salt overly sensitive (SOS), Na+/H+ exchangers (NHXs), high sodium affinity transporter (HKT) and plasma membrane protein (PMP) are activated during salinity stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 165 publications
(191 reference statements)
3
36
0
1
Order By: Relevance
“…Recently, Sun et al demonstrated that increased salinity tolerance in soybean over-expressing NHX gene reflected reduced oxidative damage and increased SOS1, SKOR, and HKT [58]. The regulated expression of NHX and SOS maintains the ratio of Na/K, thereby significantly affecting the growth under saline conditions [59,60]. Improving Na + exclusion leads to maintaining ion homeostasis in roots, thus ensuring relatively lower concentrations of toxic ions within shoot [61].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sun et al demonstrated that increased salinity tolerance in soybean over-expressing NHX gene reflected reduced oxidative damage and increased SOS1, SKOR, and HKT [58]. The regulated expression of NHX and SOS maintains the ratio of Na/K, thereby significantly affecting the growth under saline conditions [59,60]. Improving Na + exclusion leads to maintaining ion homeostasis in roots, thus ensuring relatively lower concentrations of toxic ions within shoot [61].…”
Section: Discussionmentioning
confidence: 99%
“…Ionic and osmotic imbalances and oxidative damage are caused by high levels of salinity in roots, resulting in growth retardation, withering, or death [15]. Excess ROS can cause lipid peroxidation, protein oxidation, nucleotide damage, enzyme inhibition, and the activation of programmed cell death (PCD), which are all linked to signaling since the reaction products convey information to downstream processes [1,5,16]. To scavenge high ROS levels, an efficient system of enzymatic and non-enzymatic antioxidants is involved.…”
Section: Introductionmentioning
confidence: 99%
“…the WRKY, SNAC, MYB, and DREB families are regarded as the virtual switches that directly up-regulate or down-regulate the gene expression. Up-regulation of the NAC transcription factor was observed in salinity tolerance in rice and wheat cultivars [16]. In contrast to the ATPase activity, vacuolar pyrophosphatase (H + -PPase) activity pumps H + via the vacuolar membrane, providing another major driving force for sodium accumulation in the vacuole.…”
Section: Introductionmentioning
confidence: 99%
“…In order to survive, plants adapt the highly complex ion transport network along with other stress tolerance mechanisms that play important roles in the uptake of solutes from the soil (Tang et al, 2020a). In plant cells, diverse membrane proteins are involved in the regulation of cellular uptake and efflux of inorganic ions such as Na + , K + , Ca 2+ , Cl − , and other ions (Amin et al, 2020). In addition to their role in the maintenance of cellular ion homeostasis under normal and stress conditions, they are involved in nutrient transport, membrane potential, and signal transduction (Kumar & Mosa, 2015).…”
Section: Introductionmentioning
confidence: 99%